Adenoviral vectors as novel vaccines for influenza. (5th January 2015) - Coughlan, Lynda; Mullarkey, Caitlin; Gilbert, Sarah
Abstract: Objectives: Influenza is a viral respiratory disease causing seasonal epidemics, with significant annual illness and mortality. Emerging viruses can pose a major pandemic threat if they acquire the capacity for sustained human-to-human transmission. Vaccination reduces influenza-associated mortality and is critical in minimising the burden on the healthcare system. However, current vaccines are not always effective in at-risk populations and fail to induce long-lasting protective immunity against a range of viruses. Key findings: The development of 'universal' influenza vaccines, which induce heterosubtypic immunity capable of reducing disease severity, limiting viral shedding or protecting against influenza subtypes with pandemic potential, has gained interest in the research community. To date, approaches have focused on inducing immune responses to conserved epitopes within the stem of haemagglutinin, targeting the ectodomain of influenza M2e or by stimulating cellular immunity to conserved internal antigens, nucleoprotein or matrix protein 1. Summary: Adenoviral vectors are potent inducers of T-cell and antibody responses and have demonstrated safety in clinical applications, making them an excellent choice of vector for delivery of vaccine antigens. In order to circumvent pre-existing immunity in humans, serotypes from non-human primates have recently been investigated. We will discuss the pre-clinical development of these novel vectors and their advancement to clinical trials.